Post-entry ongoing organisational changes of foreign subsidiaries and survival: Does self-selection matter? - Kim, Kyungho (Global Business and Economics Review, 2019)
This study examines the relationship between the strategy choice of organisational change and the subsequent organisational survival by accounting for the self-selection. This study employed the outward 2525 firm-year foreign direct investments by Korean textile firms from 1986 to 1995, during which labour-intensive Korean firms in the textile industry largely depend on outward foreign direct investment to explore foreign opportunities in developing countries while avoiding increasing labour costs in the domestic market. This study applied a self-selection model introduced by Heckman (1979) to test the strategy choice problem. The results without accounting for self-selection show that organisational change in product areas and investment amount have a significant and negative relationship with the mortality rate of a foreign subsidiary, while organisational change in ownership rate does not. When accounting for self-selection, however, the former effects disappear, whereas the latter effect becomes positively significant, suggesting that the effect of strategy choice of organisational change depends on whether unobserved firm attributes and environmental conditions, as well as the type of organisational change, are accounted for in the analytic model.
Keywords: Fdi; Foreign direct investment; Global business; Mortality rate; Ongoing organisational change; Self-selection; Strategy choice